Occurrence of leaf rust disease in Oxalis triangularis caused by Puccinia oxalidis in Valdivia, Chile - Rojas, Carolina; Díaz, Gonzalo A; Montenegro, Osvaldo; Ferrada, Enrique (Plant disease, 2023)
False shamrock (Oxalis triangularis), native to South America, is an ornamental and popular plant bulb, commercialized for their attractive shape and color (purple triangular leaves) (Taha et al., 2013). In Chile, a rust was detected in O. triangularis plants growing from April to June in several gardens (n=10) in the city of Valdivia, estimating a disease incidence between 80 and 100%. The symptoms appeared as diffuse chlorotic spots from the upperside of leaves, where infected tissues eventually become completely necrotic, and yellow rust pustules were observed on the underside of leaves. Severe symptoms on infected leaves were consistently observed, showing necrosis on entire leaves. Symptomatic plants (n=50) were collected, and three representative isolates from different localities (OX1, OX2, and OX3) were used for morphological and genetic identification. Uredinia (n=20) were hypophyllous, erumpent, yellow, and irregularly distributed, with sizes from 340 to 850 μm in diameter. Urediniospores (n=150) were yellow, subglobose to globose, equinulate, with measures of 14.2 - 17.7 x 14.7 - 17.2 µm. Teliospores were absent. Based on morphological characters, this rust was identified as a Puccinia sp. These morphological characteristics coincided with those indicated by Šafránková (2014), Abbasi et al. (2018), and Khouader et al. (2018). To classify this rust genetically, sequences analyses were performed using the ITS region of the rDNA (ITS4/ITS5) (White et al., 1990). The DNA was extracted using a commercial kit. The results indicated 99% similarity with two reference sequences of P. oxalidis (MH325473 and MH325474) available at GenBank (NCBI http://www.ncbi.nlm.nih.gov/BLAST/). The sequences obtained were deposited in GenBank (ON259085 to ON259087). Based on the maximum parsimony phylogenetic tree, the sequences of Chilean isolates were clustered with those of P. oxalidis references. Pathogenicity tests were conducted using three isolates (OX1 to OX3). Surface disinfection of leaves of O. triangularis (n=36 plants), were performed by spraying 1% NaOCl solution for 1 min. Subsequently, 2 mL of urediniospores suspensions of each isolate (OX1 to OX3) at a concentration of 106 urediniospores/mL, were sprayed with an atomizer on the underside of the leaves of all plants. Urediniospores were obtained following the methodology proposed by Ferrada et al. (2020). Control leaves were disinfested and inoculated with sterile distilled water. Plants of O. triangularis of 90-day-old were incubated in a humid chamber (24°C, 80% HR), with a photoperiod of 12 light /12 dark. At 11 days post-inoculation, all leaves inoculated developed chlorosis spots and pulverulent pustules (averaged 10.9 to 25.4 pustules per leaf), and then at 26 days post-inoculation, affected leaves showed necrotic tissues. The identity of these isolates was confirmed morphologically. The symptoms in the control leaves were negative. To our knowledge, this is the first report of multiple occurrences of the leaf rust disease on gardens of false shamrock caused by P. oxalidis in Valdivia, south of Chile. Previously, P. oxalidis has been reported to cause leaf rust disease in O. triangularis in the Czech Republic (Šafránková, 2014) and O. debilis in Korea (Lee et al., 2018). The leaf rust disease could represent a threat to the ornamental gardens of O. triangularis in Valdivia. Currently, epidemiological studies of leaf rust disease are necessary to develop management strategies in gardens of O. triangularis.